The Protein Alpha-Synuclein: Its Normal Role (in Neurons) and its Role in Disease - Manfredsson, Fredric P.; Perez, Ruth G.; Martinez Sandoval, Ivette (Frontiers Media SA, 2020)
The protein alpha-synuclein (α-syn) is by far the most vetted pathogenic participant in the neurodegeneration that occurs in Parkinson's disease (PD) and other synucleinopathies such as multiple system atrophy (MSA). Although the precise role of this protein in disease pathogenesis is unknown, its toxicity is largely considered to be due the formation of toxic intracellular aggregates. As such, targeting α-syn directly is being heavily investigated as a potential therapeutic avenue in PD. Nevertheless, the precise normal function(s) of this protein in neurons of the central and autonomic nervous systems (and other cells) is largely unknown, and a multitude of work has shown that removing this protein from neurons also has a profound effect on a variety of intracellular processes, and in some cases leads to neurodegeneration. Such findings have led some to postulate that α-syn has certain functions that are crucial to some populations of neurons, and that perhaps its role in disease can be explained as a toxic loss of function as a result of its sequestration into aggregates. Regardless of the precise role of α-syn in disease, it is crucial that the role of this protein in normal neuronal function is thoroughly defined as the field moves forward with α-syn modulating therapies. Indeed, α-syn is one of the most abundant proteins of the nervous system, and can be found both centrally and in the peripheral nervous system. Although this protein is most often associated with a role in neurotransmission, a plethora of work has attributed a role of α-syn to disparate functions such as mitochondrial function, neurotransmitter production, and calcium homeostasis, amongst others. This Research Topic collects articles which look at α-syn function, both in the context of a healthy neuron, functional changes of this protein with aging, and in disease.